Unboxing The Black Box On The Dimensions Of Social Globalisation And The Efficiency Of Microfinance Institutions In Asia - Hafezali Iqbal Hussain; Katarzyna Szczepańska-Woszczyna; Fakarudin Kamarudin; Mohd Haizam Mohd Saudi; Nazratul Aina Mohamad Anwar (Instytut Badań Gospodarczych, 2024)
Research background: Microfinance institutions (MFIs) play an important role in alleviating poverty. Thus, MFIs should be efficient in order to ensure that their objectives on social welfare and financial performance can be achieved by identifying the potential determinants, specifically on social globalisation. Purpose of the article: This paper examines the impacts of the social globalisation dimensions of interpersonal, informational, and cultural globalisations on the financial and social efficiency of MFIs. Methods: The data period covered the years 2011–2018; the data set consists of 176 MFIs from six Asian countries. The Data Envelopment Analysis (DEA) approach was employed to examine the MFIs’ efficiency levels. Generalised Least Square (GLS) regressions were used to analyse the impacts of social globalisation and other determinants towards the efficiency of MFIs. Findings and value added: Interpersonal globalisation had a significantly negative correlation with social efficiency, suggesting that increasing the number of foreigners in management in-trudes on local managers’ decisions. Informational globalisation had a significantly positive correlation with financial and social efficiency, which signifies that more information produces monopolistic profits in this industry. Finally, cultural globalisation had a positive correlation withsocial efficiency, demonstrating that a global trading culture improves the abilities and technolog-ical skills for labour development and enhances MFIs’ social efficiency. In general, the Cobb Douglas Production theory explained the understanding of the impacts social globalisation has on MFI efficiency. Furthermore, the findings from this study could provide important scientific, practical gap and contribute new insights and implications to various parties. Firstly, governments or policymakers can establish effective national policies and strategies. Secondly, this study could support investors in monitoring and understanding the performance of MFIs. Finally, the research could fill scholarly gaps and uncover more potential factors that influence the efficiency of MFIs.